Ti MINERALS IN ORES AND SKARNS OF THE AKTASH MAGNETITE-POLYMETALLIC DEPOSIT, WESTERN KARAMAZAR, TAJIKISTAN - U.A. Yatimov; I.A. Blinov; M.A. Rassomakhin; S.M. Lebedeva; N.S. Safaraliev (Минералогия)
The article characterizes Ti minerals from different mineral assemblages of the Aktash magnetite-polymetallic deposit (Western Karamazar, Northern Tajikistan). Anatase, ferrous pyrophanite, perovskite, calzirtite, zirconolite and titanite are described in ores of the deposit and most of these minerals are found for the first time in both the Aktash deposit and the entire Karamazar region. The minerals are identified using optical and electron microscopy. The presence of anatase, pyrophanite, perovskite and titanite is also confirmed by Raman spectroscopy. Perovskite and calzirtite are found in serpentine-phlogopite-calcite skarns, anatase, pyrophanite, perovskite, zirconolite and titanite are determined in serpentine-garnet-pyroxene skarns, which host galena-sphalerite ores, and pyrophanite and titanite are identified in sulfide-magnetite ores. Based on mineral assemblages and relationships, it is concluded that perovskite, calzirtite, and zirconolite formed at the beginning of the skarn stage, which is followed by the formation of anatase, pyrophanite, titanite and zircon.